An evaluation of messenger RNA competition in the shutoff of human interferon production. - Sehgal, P B (1976)
The process that shuts off poly(I)-poly(C)-induced interferon production in a strain of diploid human fibroblasts (FS-4)-involves the synthesis of new RNA, presumably nuclear heterogeneous RNA. When cultures in the shutoff phase of interferon production are treated with actinomycin D (5 mug/ml) or 5,6-dichloro-1-beta-D-ribofuranosylbenzimidazole (DRB 40 muM), the rate of interferon production continues to decline for a further 3-4 hr, but then tends to level off. The treated cultures maintain interferon production at a reduced level for at least 10 hr. The residual rate of interferon production is higher in cultures which received actinomycin D or DRB early in the shutoff phase as compared to the rate in cultures treated late.